RELIGIOUS MONOGRAMS AND SYMBOLS - Kochumuttom, Thomas (Journal of Dharma, 1984)
The place of symbols and monograms in religion is beyond dispute. Religion necessarily involves faith in supernatural factors. Even in the so-called natural religions there is the recognition of realities which are beyond human reasoning, and as such they are accepted not as logical conclusions but as revelations from above demanding man to believe. This implies that every religion invariably points to certain factors which are beyond the human comprehension and expression; or rather in religious life man necessarily comes to a point beyond which his reason and language cannot go, although his experience becomes religious in the strict sense only when it touches on realities beyond that point. Consequently revelation and faith, however differently they may be defined, are basic elements in all religions, and this compels the use of symbols in religious ritualsr and discourses: objects of revelation and faith being incomprehensible in human concepts, and inexpressible in human terms, one is forced to employ symbols to explain and express them. Thus, symbols become necessary tools for man to understand and communicate truths that are per se religious.